Diabetes biomarkers - Sattar, Naveed (Henry Stewart Talks, 2013)
For what reason do we need further biomarker research in diabetes?, Prediction of diabetes, Prediction of complications, Personalized therapy, Biomarkers role in understanding the pathophysiology of diabetes, Biomarkers and genetics